Relationship between miRNA and ferroptosis in tumors - Dai, Shang-Ming; Li, Feng-Jiao; Long, Hui-Zhi; Zhou, Zi-Wei; Luo, Hong-Yu; Xu, Shuo-Guo; Gao, Li-Chen (Frontiers in Pharmacology, 2022)
Malignant tumor is a major killer that seriously endangers human health. At present, the methods of treating tumors include surgical resection, chemotherapy, radiotherapy and immunotherapy. However, the survival rate of patients is still very low due to the complicated mechanism of tumor occurrence and development and high recurrence rate. Individualized treatment will be the main direction of tumor treatment in the future. Because only by understanding the molecular mechanism of tumor development and differentially expressed genes can we carry out accurate treatment and improve the therapeutic effect. MicroRNA (miRNA) is a kind of small non coding RNA, which regulates gene expression at mRNA level and plays a key role in tumor regulation. Ferroptosis is a kind of programmed death caused by iron dependent lipid peroxidation, which is different from apoptosis, necrosis and other cell death modes. Now it has been found that ferroptosis plays an important role in the occurrence and development of tumors and drug resistance. More and more studies have found that miRNAs can regulate tumor development and drug resistance through ferroptosis. Therefore, in this review, the mechanism of ferroptosis is briefly outlined, and the relationship between miRNAs and ferroptosis in tumors is reviewed.